PENGARUH REMUNERASI TERHADAP KINERJA PEGAWAI KANTOR PELAYANAN PAJAK PRATAMA TUBAN - ANHARUDIN AZIS (Universitas Negeri Surabaya, 2013)
ABSTRACT Tax Office Primary Tuban is one of the government offices under the Directorate General of Taxation II East Java provincial office is implementing a program of bureaucratic reform. The bureaucratic reform program include improved payroll system (remuneration) granted to employees. In fixing the payroll system intended, implemented through the provision of salaries, honoraria, allowances remain, bonuses, incentives, severance and retirement. Improved remuneration fairer and balanced is expected to improve employee performance and overall agency performance, although in practice there are still some problems both internal and external into the organization. This research aims to examine and determine the effect of remuneration on the performance employee Tax Office Primary Tuban. The research method used is associative with a quantitative approach. Data collection techniques used were enclosed questionnaire. The population in this study were all employees of the Tax Office Primary Tuban with a total sampling is used then this is the overall sample totaling 52 employees. Independent variable in this study was Remuneration (X) and Employee Performance (Y) as the dependent variable. Analysis model of the data in this study are product moment correlation test, t test and simple linear regression as a test of the hypothesis. Confidence level used is 95% (α = 0,05). Test results using product moment correlation coefficient r of 0.860 which indicates that the variable remuneration is very strong and positive effect on employee performance. Whereas the t-test also showed variable remuneration significant effect on employee performance because tvalue > ttable of 11.924 with significance value of 0.000a. The coefficient of determination (R2) obtained 0.739 or 73.9%. With Thus the changes on officer performance caused by salaries, honorarium, allowance, bonus, incentives, severance and pensions with the influence amounting to 73.9% and the rest 26.1% influenced by other variables. While the regression equation in this study is Y = 9.986 +1.252 X. This research proves that there is a positive and significant impact between employee performance to remuneration Tax Office Primary Tuban. Keywords: Remuneration, Employee Performance.